Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1080/00952990.2016.1229324
|View full text |Cite
|
Sign up to set email alerts
|

A review of implicit and explicit substance self-concept as a predictor of alcohol and tobacco use and misuse

Abstract: Background This paper provides an overview of the self-concept as it relates to substance use. Self-concept has a long history in psychological theory and research; however, substance self-concept (e.g., viewing one’s self as a drinker or smoker) is an understudied area of research with the potential to expand existing conceptualizations of substance use, addiction, and prevention and treatment efforts, and should receive greater research attention. Objectives First, we review and provide a theoretical frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
59
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 104 publications
(79 citation statements)
references
References 68 publications
(102 reference statements)
6
59
1
2
Order By: Relevance
“…The DI-IAT was also positively associated with both typical consumption and hazardous drinking after controlling for explicit drinking identity replicating previous studies (Lindgren et al, 2016a), which may add some confidence that the study’s novel findings will replicate.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The DI-IAT was also positively associated with both typical consumption and hazardous drinking after controlling for explicit drinking identity replicating previous studies (Lindgren et al, 2016a), which may add some confidence that the study’s novel findings will replicate.…”
Section: Discussionsupporting
confidence: 83%
“…IATs are computer-administered reaction time tasks thought to assess the relative strength of associations between constructs held in memory and have demonstrated utility for predicting hazardous drinking, often predicting above and beyond self-report questionnaires (for reviews, see Lindgren, Neighbors, Gasser, Ramirez, & Cvencek, 2016a; Reich, Below, & Goldman, 2010). The Drinking Identity IAT (DI-IAT; Lindgren et al, 2013b) assesses the relative associations between the constructs me (stimuli: me, my, mine, and self) and not me (stimuli: they, them, theirs, other) with the constructs drinker (stimuli: drinker, drink, drunk, and partier) and non-drinker (stimuli: non-drinker, abstainer, sober, and abstain).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is contrary to previous work using implicit and explicit measures of drinking identity (e.g., Lindgren et al, 2013b; 2016c) as well as findings from meta-analyses of implicit and explicit measures (e.g., Greenwald, Poehlman, Uhlmann, & Banaji, 2009), which tend to report correlations around .25. Given previous findings – both in the alcohol and substance use domain as well as in other areas of psychology – that implicit and explicit measures of identity are reliable and robust predictors (see Back et al, 2009; Greenwald & Farnham, 2000; Lindgren et al, 2016d), we suspect that the weaker relationships observed here – including the implicit and explicit measures' relations with one another and with hazardous drinking – reflect the need to improve the centrality measures and stimuli versus their ultimate inability to capture meaningful aspects of identity (whether via self-report or reaction time measures). However, additional research will clearly be needed to test this supposition.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these findings could be justified by the positive effect of the practice of PA in women, decreasing the negative effect of tobacco on VO 2MAX . With respect to self-concept, it has been proven that alcohol intake is negatively related to it, since Chacón et al [66] and Lindgren et al [68] establish the negative relationship of this substance with its familiar, academic and physical dimensions. In these studies, only positive relationships were found with the social dimension of self-concept.…”
Section: Discussionmentioning
confidence: 99%